Promoting the spiritual well-being of children and young people with special needs - Robin Jackson; Angelika Monteux (Scottish Journal of Residential Child Care)
Last year Camphill-Rudolf Steiner-Schools in Aberdeen hosted a conference entitled Promoting the Spiritual Well-being of Children and Young People with Special Needs: an Inclusive Vision. The conference, which formed part of the National Debate on Education and was financially supported by the Scottish Executive, arose from a recognition that the spiritual dimension in a child's development continues to be neglected.